Penguatan Moral dan Agama Anak Usia Dini Melalui Pembiasaan Sholat Dhuha di TK Negeri Pembina Ponorogo - Nurtina Irsad Rusdiani; Linda Setyowati; Nanda Putri Agustina; Nurleha Nurleha; Ardhana Januar Mahardhani (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2023)
It is very important to strengthen morals and religion from an early age. If the inculcation of religious values has been instilled from an early age, children will have the provision to carry out religious activities and habits easily. This is also done by Pembina Ponorogo Public Kindergarten through the habit of Dhuha Prayer. The research was conducted at TK Negeri Pembina Ponorogo with the informants being the Principal and Teacher Staff at the TK Negeri Pembina Ponorogo, the data collection methods used in this study were observation, interviews, and documentation. From the results of the study it is known that strengthening the morals and religion of early childhood through the habit of Dhuha Prayer at TK Negeri Pembina Ponorogo has an impact on the formation of children's character which can be seen from changes in children's behavior, namely: (1) children have a sense of gratitude, (2) children have religious characteristics , and (3) children are more disciplined with time.